Pirates without borders: The propagation of cyberattacks through firms’ supply chains - Crosignani, Matteo; Macchiavelli, Marco; Silva, André F. (Journal of Financial Economics, 2023)
This paper examines the supply chain effects of the most damaging cyberattack in history so far. The attack propagated from the directly hit firms to their customers, causing a four-fold amplification of the initial drop in profits. These losses were larger for affected customers with fewer alternative suppliers. Internal liquidity buffers and increased borrowing, mainly through bank credit lines, helped firms navigate the shock. Nonetheless, the cyberattack led to persistent adjustments to the supply chain network, with affected customers terminating trading relations with directly hit firms and forming new ones with alternative suppliers with a stronger cybersecurity posture.